Expressive properties of internet evolutionized malay words within the dimension of malay values and attitudes - Abd. Rozan, Mohd. Zaidi; Nagano, Robin; Mikami, Yoshiki (2009)
Internet Evolutionized Malay (EM) is a newly formed language variety that has gained popularity within online text-based Malay communities. This paper discusses a study that utilized nine EM words and five of their corresponding Standard Malay (SM) words as word stimuli, with responses of 56 respondents towards 15 adjective pairs. The expressive properties or connotative meanings of the stimuli were then analyzed by means of Semantic Differential Analysis (SDA) to quantify the Type and Level of adjective-pairs. Based on the analysis, our investigation reveals two findings: 1) Different types of connotations of SM and EM words are observed, which are particularly common when the words pertain to emotional description of human character, and 2) Level of connotation differs, where native Malay speakers have a wider spectrum of perception for SM and EM words, showing higher sensitivity to the spelling changes on SM, while non-native Malay group shows less reaction to the change. It is important to note from this study that EM is not simply being exotically spelled as ‘eye-candy’ as always argued, but also triggers different perceptual connotations.